Associated factors affecting the successful pregnancy rate of Intrauterine Insemination at International Islamic University Malaysia (IIUM) Fertility Centre - Abdul Wahab, Azantee Yazmie; Zainuddin, Ahmad Murad; Ramli, Roszaman; Mohd Yatim, Hayati; Md. Ariffin, Norsina (Malaysian Medical Association, 2011)
SUMMARY Purpose: The aim was to determine pregnancy rate and its associated factors in Intrauterine Insemination (IUI) at IIUM Fertility Centre. Methods: A retrospective analysis of 504 IUI cycles was conducted on all available records of infertile couples who had undergone IUI treatment at IIUM Fertility Centre between 2004 until 2008. The data was collected and then analyzed with multivariate logistic test with a significant level of 0.05. Results: The overall clinical pregnancy rate was 14.5% (73/504). Among 73 pregnancies, 44 cases were live births (60%), 23 cases were miscarriages (32%) and 6 were ectopic pregnancies (8%). Analysis from logistic regression revealed two predictive variables which influence the pregnancy; female age (OR:0.580, CI:0.338- 0.996, p=0.046) and male sperm count (OR:0.506, CI:0.304- 0.843, p=0.008). Pregnancy weren’t related to the etiology of infertility, duration and type of infertility, cycle number of IUI, ovarian stimulation protocol and the number of dominant follicle. Conclusion: IUI remain as a convenient and useful treatment option in women of younger age (<30 years) and male with higher sperm count (≥100 million per ml). KeY WORdS: IUI, Pregnancy rate, Maternal age, Motile sperm count